PENETAPAN FLAVONOID TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN CENGKEH (Syzygium aromaticum (L). Merr) DAN DAUN SALAM (Syzygium polyanthum Thwaites) - Mia Aklimah; Meiliza Ekayanti (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Syzygium aromaticum and Syzygium polyanthum are species of the Myrtaceae family. Clove leaves and bay leaves contain active compounds, namely flavonoids. This research was conducted with the aim of knowing the total flavonoid content and antioxidant activity of the ethanol extract of clove (Syzygium aromaticum) and bay (Syzygium polyanthum) leaves. The extraction method used in this research is cold extraction in the form of maceration with the choice of solvent, namely 96% ethanol. The total flavonoid content test was carried out using the colorimetric method while the antioxidant activity test used the DPPH (1,1-diphenyl-2-picridhydrazil) method. The results of total flavonoid content of clove leaf ethanol extract and bay leaf ethanol extract were 206.447 mgQE/g and 165,658 mgQE/g.. The IC50 for clove leaves was 3.026 μg/mL and the IC50 for bay leaves was 3.555 μg/mL. The conclusion of the study was that the extract from clove leaves on total flavonoid levels and antioxidant activity tests had the highest value.